The Usage of Arcs Radii Profile Variation for the Synthesis of Railway Wheel and Rail Head Profiles - Tomas Lack; Juraj Gerlici (Communications - Scientific letters of the University of Zilina, 2006)
The presented article deals with one of the ways of profile geometry design of a railway wheel and railhead. The base for the creation of new profiles is an interactive attitude based on the modification of “the original shape which is defined by section of a railway wheel profile”, with to each other connected and exactly defined arcs radii. It is possible to change them according to shape needs of the final geometrical characteristics.